2013
DOI: 10.1524/ract.2013.2090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a spacer moiety on radiometal labelled Neurotensin derivatives

Abstract: Neurotensin / NT(8-13) / Radiotracer / Lu-177 / DOTA / Spacer moietySummary. The binding sequence of the regulatory peptide Neurotensin, NT(8-13), represents a promising tumourspecific vector for the development of radiopeptides useful in nuclear oncology for the diagnosis (imaging) and therapy of cancer. A number of radiometal-labelled NT(8-13) derivatives have been reported, however, the effect of the spacer which connects the vector with the radiometal complex has yet not been investigated systematically. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…We previously reported that the introduction of a hydrophilic spacer made of a tetraethylene glycol (PEG 4 ) moiety between the tumor‐targeting peptide NT(8–13) and the radiometal complex based on the universal macrocyclic chelator 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid (DOTA) improves the cell‐internalization properties, receptor affinity, and metabolic stability of conjugate NT 1 (Table and Figures –) . Therefore, we used the general structure NT 2 as a reference for further investigations of the effect of amino acid substitutions on the peptide sequence NT(8–13).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We previously reported that the introduction of a hydrophilic spacer made of a tetraethylene glycol (PEG 4 ) moiety between the tumor‐targeting peptide NT(8–13) and the radiometal complex based on the universal macrocyclic chelator 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid (DOTA) improves the cell‐internalization properties, receptor affinity, and metabolic stability of conjugate NT 1 (Table and Figures –) . Therefore, we used the general structure NT 2 as a reference for further investigations of the effect of amino acid substitutions on the peptide sequence NT(8–13).…”
Section: Resultssupporting
confidence: 92%
“…[a] Calculated values. [b] Observed ESI‐HRMS data: [ M +2 H + ] 2+ ; preliminary data on compounds NT‐1 , 2 , and 3 were reported previously …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, NTR1-targeted peptides have been labeled with a number of clinically relevant radiometals, such as 99m Tc, 111 In and 68 Ga[11,15,2123]. In recent years, 177 Lu, a theranostic radioisotope, has received increasing attention for potential clinical applications due to its dual emission characteristics[2427].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the NT‐XIX peptide was labeled with rhenium‐188 (half‐life of 17.0 hours, β‐energy of 2.12 MeV) by forming the 188 Re‐tricarbonyl complex, as already mentioned in the above chapter concerning Tc‐99m (entry 10, Table ). The first peptides labeled with Lu‐177 were reported by the Mindt group, who investigated the effect of different spacers (X), such as Ahx (aminohexanoic acid) and PEG 4 (tetraethylene glycol), on the physicochemical properties of a small series of peptides (entry 1, Table ) with a specific focus on the impacts on lipophilicity, stability in vitro in serum, and receptor affinity and internalization . Most importantly, the peptide with the PEG 4 ‐spacer linked to the DOTA chelator was found to have a more favorable receptor affinity by a factor of 4 compared with NT(8–13) without the spacer, and the presence of the spacer did not significantly affect the lipophilicity of the peptide.…”
Section: Introductionmentioning
confidence: 99%